Comparative Analysis Study Of ATC-40 and SNI 1726-2012 Guidelines for Beam Structure Performance and Column Trans Studio Apartments Applications Using Dynamic Response Spectrum Analysis Methods - Munthe, Agyanata Tua; Gafur, Abdul (Journal of Applied Science, Engineering, Technology, and Education, 2019)
The earthquake that often hit Indonesia caused thousands of lives and caused damage to buildings. These earthquakes often occur because Indonesia is in two regions, namely the Pacific earthquake path (Circum Pacific Earthquake Belt) and the Asian earthquake lane (Trans Asiatic Earthquake Belt). Earthquake disasters cause damage to building structures. When an earthquake occurs, it is expected that the building can accept earthquake force at a certain level without significant damage to its structure. In general, earthquake analysis is divided into two major parts, namely static earthquake analysis and dynamic earthquake analysis. In buildings that are very high, irregular, multilevel, and buildings that require enormous accuracy are used dynamic analysis planning, which consists of a variety of spectral response analysis and dynamic time response dynamic analysis. This study aims to determine the building's security in terms of displacement, drift, and base shear. The method used is a dynamic analysis of the response spectrum using the ETABS program. The maximum total drift in the X direction is 0.0200475 m and in the Y direction is 0.020405 m, so the building is safe against ultimate boundary performance (0.02h) and service boundary performance {(0.03 / R) x h}. So that the displacement in the building does not exceed the maximum displacement, the building is safe from earthquake plans.